Adherence to the Healthy Nordic Food Index and the incidence of acute myocardial infarction and mortality among patients with stable angina pectoris. Issue 1 (8th August 2018) - Puaschitz, N. G.; Assmus, J.; Strand, E.; Karlsson, T.; Vinknes, K. J.; Lysne, V.; Drevon, C. A.; Tell, G. S.; Dierkes, J.; Nygård, O.
Abstract: Background: The Healthy Nordic Food Index (HNFI) has been associated with beneficial effects on markers of cardiovascular disease (CVD). Whether such effects are present among patients with established coronary heart disease is unknown. In the present study, we investigated the association between adherence to the HNFI and the risk of acute myocardial infarction (AMI) (fatal or nonfatal) and death among patients with stable angina pectoris. Methods: In the Western Norway B‐vitamin Intervention Trial, participants completed a 169‐item semi‐quantitative food frequency questionnaire. The HNFI was calculated from six food groups (fish, cabbage, apples/pears, root vegetables, whole grain bread and oatmeal), scoring 0–6. Three adherence groups were defined: 0–1 points (low), 2–3 points (medium) or 4–6 points (high). Cox regression analyses investigated associations between adherence to the HNFI and outcomes. Results: Among 2019 men (79.7%) and women with mean age of 61.7 years, 307 patients experienced an AMI event during a median (25th and 75th percentiles) follow‐up of 7.5 (6.3 and 8.7) years. Median follow‐up for total mortality was 10.5 (9.3 and 11.7) years; 171 patients died from CVD and 380 from any cause. No association between HNFI and the risk of AMI was detected. However, the HNFI was associated with a reduced risk of all‐cause death, both by linear estimates [hazard ratio (95% confidence interval = 0.91 (0.84–0.98)] and by comparison of the highest with the lowest adherence group [hazard ratio (95% confidence interval = 0.70 (0.52–0.95)]. Conclusions: The results of the present study suggest that a Healthy Nordic diet may reduce mortality in patients with established CVD.